2022
DOI: 10.3389/fruro.2022.877521
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Reported Experience With Pediatric Urology Telemedicine Visits During the COVID-19 Pandemic

Abstract: IntroductionTelemedicine has had a slow integration into surgical subspecialties like urology. Little data exists on its effect on urologic patient-provider rapport nor long term clinical outcomes. The purpose of this study was to assess the feasibility and parent-reported experience with telemedicine visits in a tertiary pediatric urology practice during the COVID-19 pandemic.MethodsParents/guardians of pediatric urology patients who were seen via telemedicine between March 12th - October 30th, 2020, at Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…22 Furthermore, our finding is lower than previous Indian and American studies that documented that more than 90% of the caregivers were satisfied with the quality of service, convenience, and benefits of teleconsultation in Indian 13 and American settings. 3 It was also quite different from the parents' satisfaction (94.2%) observed with pediatric urology telemedicine in American context 12 and the level (80.5%) reported in Italy. 23 The discrepancies in satisfaction profiles across the different settings can be justified by multiple reasons.…”
Section: Factors Associated With Caregivers' Satisfactionmentioning
confidence: 70%
See 2 more Smart Citations
“…22 Furthermore, our finding is lower than previous Indian and American studies that documented that more than 90% of the caregivers were satisfied with the quality of service, convenience, and benefits of teleconsultation in Indian 13 and American settings. 3 It was also quite different from the parents' satisfaction (94.2%) observed with pediatric urology telemedicine in American context 12 and the level (80.5%) reported in Italy. 23 The discrepancies in satisfaction profiles across the different settings can be justified by multiple reasons.…”
Section: Factors Associated With Caregivers' Satisfactionmentioning
confidence: 70%
“…Moreover, almost all of the teleconsultations carried out in the present study setting were cellphone-based audio calls, unlike that of developed countries, where formal high-end video conferencing systems exist along with the features of store-and-forward of images. 12,13 The difference might also be because our study involved resident physicians who lacked preexisting relationships with patients and their caregivers, while other studies involved primary care providers who had established long-standing rapport with their patients. 18 On the other hand, this study showed that female caregivers were much more likely than men to be satisfied with teleconsultation service.…”
Section: Factors Associated With Caregivers' Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation